THE DEVELOPMENT OF AN OPERATIONAL AREA USING PARTICIPATORY LEARNING PROCESSES IN THE THUNG KHRU-BANG KHUN THIAN COMMUNITIES, BANGKOK - Phutimatee, Kanchanee; Chutataweesawas, Sirikoy; Pecthnin, Surat; Tanchareon, Sumate; Prathumwong, Wilaiwam (Journal of Social Science and Cultural, 2024)
This research aimed to 1) explore the context and challenges of community learning spaces, 2) design appropriate spaces and learning activities, and 3) establish guidelines for the physical development of these learning spaces through participatory action research. The study employed a qualitative approach, with purposive sampling used to select key informants, including 1) seven learning space owners, 2) five teachers, 3) thirteen parents, and 4) three activity organizers, for 28 participants. Research tools comprised 1) a survey and evaluation form for learning spaces, 2) an interview guide for teachers, and 3) an interview guide for parents. The research process involved gathering relevant documents, conducting surveys, interviews, focus group discussions, and organizing community forums. The data were analyzed using content analysis, leading to comprehensive conclusions. The findings revealed that community learning spaces should be developed in two key areas: physical space and learning activities. The design of these spaces should reflect the community's identity, ensuring they are convenient, safe, and accessible to all age groups, and that they incorporate two essential development elements: 1) fostering participatory engagement, and 2) considering five key factors for the collaborative development of learning spaces and activities within the community. These factors include 2.1) safety, 2.2) connectivity to transportation, 2.3) environmental conditions inside and outside the learning space, 2.4) strategies for improving physical learning spaces, and 2.5) skills in managing both the space and the learning processes. The study also recommends promoting the use of public transportation to connect learning spaces within the community, enhancing the business potential of these spaces, and integrating community-based curricula with schools and educational institutions. Additionally, the development of a collaborative network involving local entrepreneurs, alongside partnerships with both public and private sectors, is crucial for fostering a sustainable and comprehensive learning ecosystem.